Fecundity of Sebastes mentella and Sebastes norvegicus in the Irminger Sea and Icelandic waters - Saborido-Rey, Fran; Domínguez-Petit, Rosario; Garabana, Dolores; Sigurdsson, Thorsteinn (Ciencias Marinas, 2015)
18 pages, 6 figures, 2 tables [EN] Fecundity of redfish Sebastes mentella and Sebastes norvegicus in the Irminger Sea and Icelandic waters was analyzed in relation to several maternal features and oocyte developmental stages. The mean potential fecundity in S. norvegicus was estimated to be 123,300 oocytes and relative fecundity averaged 116 oocytes g–1. Mean potential fecundity in S. mentella was 50,013 oocytes and relative fecundity was 64 oocytes g–1. Strong fecundity down-regulation (50% on average) was observed during oocyte development estimated from September to November, when oocytes reached the advanced stage of vitellogenesis. This result implies that fecundity can only be comparable between individuals presenting the same stage of oocyte development. However, the development rates differed between species and between stocks, and therefore the same stage is reached at a different time of the year. Fecundity varied significantly with female weight and length, while condition had little influence on fecundity variation [ES] La fecundidad de la gallineta nórdica, Sebastes mentella y Sebastes norvegicus, en el mar de Irminger y aguas de Islandia se analizó en relación con diversas características maternales y durante diferentes periodos del desarrollo ovocitario. La fecundidad potencial de S. norvegicus se estimó en 123,300 ovocitos con una fecundidad relativa de 116 ovocitos g–1. La fecundidad potencial promedio de S. mentella fue de 50,013 ovocitos con una fecundidad relativa de 64 ovocitos g–1. Sin embargo, se observó una fuerte regulación decreciente de la fecundidad (un promedio del 50%) durante el desarrollo ovocitario estimado entre septiembre y noviembre, cuando los ovocitos alcanzaron la vitelogénesis avanzada. Este descenso implica que la fecundidad sólo se pueda comparar entre individuos que se encuentren en el mismo estado de desarrollo ovocítico. Sin embargo, la tasa de desarrollo ovocitario fue diferente para cada especie y población, y por tanto el mismo estado se alcanza en diferentes ...